PENERAPAN MODEL PEMBELAJARAN NUMBER HEAD TOGETHER PADA METODE PERMAINAN RANDOM WELL UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS 5 SDN TAMBAKREJO DI MASA PANDEMI COVID 19 - Nurmalitasari, Ajeng Nisa (Jurnal Analisis Pendidikan Sosial, 2024)
This study aims to increase student activity in the thematic learning process for grade 5 students at SDN Tambakrejo in the 2020/2021 academic year. Less than optimal student activity is caused by distance learning that is currently being carried out by teachers and students due to the pandemic. The subjects of this study were the 5th grade students of SDN Tambakrejo with a total of 32 students and 5th grade teachers. The data collected included the results of student activity questionnaires and the results of student observations. This research is a Classroom Action Research (CAR) which was carried out in two cycles. Each cycle includes 4 (four) stages, namely planning, implementing actions, observing and reflecting. In this study, it is said to be successful if the results of student activity have increased by 75%. The results showed that the second cycle could be achieved. Based on the results of the questionnaire, it was shown that the average of 3 indicators was 59%, cycle 1 was 65%, and cycle 2 was 79%. In cycle 2 it reached 79% and has exceeded the level of achievement of 79%. From the results of these data shows the results of student activity in cycle II have been able to meet the achievement indicator, namely an increase in student activity by 75%.